Philosophy of Education: contemporary critical issues - Alexandre Anselmo Guilherme (FahrenHouse, 2018)
Where does philosophy of education take us? In the social, political and cultural turmoil of the present age, it can be argued that our social imagination might be confined, and our political subverted. In response to this, some philosophers of education have strived to reveal many ideologies at work in modern myths such as the orders of educational progression, of equality of opportunity, and of the power of measurement. But is there something beyond what Paul Ricoeur called the «desert of criticism» (Ricoeur. The Symbolism of Evil)? How helpful and effective have these criticisms of our modern age been? In this editorial, an introduction to the special issue of Philosophy of Education: Contemporary Critical Issues, I discuss the importance of a critical attitude in education, and philosophy of education, whilst making reference to the works of Ilan Gur-Ze'ev and David Carr.